Cooperative knowledge processing: The key technology for future organizations - Stefan Kirn (Westfälische Wilhelms-Universität Münster, Institut für Wirtschaftsinformatik, 1995)
Drawing from the challenges organizations are faced with today, there is a growing understanding that future market success, and long-term survival of enterprises will increasingly be related to the effectiveness of information technology utilization. This, however, requires to intertwine much more seriously organizational theory and research in information processing as it has been done before. Within this paper, we approached this aim from the perspective of radically decentralized, computerized enterprises. We further assume that organizations are increasingly process-oriented, rather than applying to structuring organizations based on task decomposition and assignment. This scenario reveals that, due to the inherent autonomy of organizational units, the coordination of decentralized organizational activities (workflows, processes) necessitates a cooperative style of problem solving. On this basis, the paper introduces into the research area of cooperative knowledge processing, with a particular focus on multi-agent decision support systems, and human computer cooperative work. Finally, several important organizational applications of cooperative knowledge processing are presented that demonstrate how future enterprises can take great advantage from these new technologies.
Keywords: 650